MOBILE HEALTH APPLICATION - PREVENTING PATIENTS OF BREAST CANCER POST-TREATMENT FROM UPPER LIMB DYSFUNCTION (ULD) (Chemotherapy, Radiotherapy, and Surgery) : LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v1i2.29 - hendra dwi cahyono; Rr. Tutik sri hariyati (International Journal of Nursing and Health Services (IJNHS), 2018)
Background. Breast cancer is the most common cancer which attacks 2.1 million women annually. The high incidence of ULD is a negative impact that affects the quality of life of patients. m-Health Application is a tool that can facilitate the process of service or health care. Purpose. To know the effectiveness of m-Health Application usage in preventing Upper Limb Dysfunction (ULD) by increasing physical activity of patients after breast cancer treatment. Method. Relevant articles that were published between 2013 and 2018 were retrieved from EBSCOhost, Scopus, ScienceDirect, ProQuest, and SAGE databases, using keywords like mobile health application, breast cancer, physical activity, upper limb dysfunction. Results. This study uses 9 literatures, including 3 journals with randomised controlled trial (RCT) design, 1 quasi-experimental journal, 1 cross-sectional journal, 1 journal using a pilot study, and 1 journal using qualitative design alongside with focus group method. Almost all literatures show positive results of mobile health application in increasing physical activity of breast cancer patients. Conclusion. Mobile health application can significantly prevent the occurrence of ULD by increasing the practice of patients' physical activity through application features, such as video, games, SMS, telephone, e-mail, and the internet web. Keywords mobile health application, breast cancer, physical activity, upper limb dysfunction.